1996
DOI: 10.1164/ajrccm.153.2.8564092
|View full text |Cite
|
Sign up to set email alerts
|

Differences in interleukin-8 and tumor necrosis factor-alpha in induced sputum from patients with chronic obstructive pulmonary disease or asthma.

Abstract: Asthma and chronic obstructive pulmonary disease are characterized by chronic airway inflammation. Studies using bronchoalveolar lavage (BAL) have shown an increased proportion of eosinophils in the BAL fluid from asthmatics compared with that from normal subjects, whereas studies of chronic obstructive pulmonary disease (COPD) have shown increased numbers of neutrophils. Induced sputum allows sampling of respiratory tract secretions from patients and control subjects, providing a noninvasive method of studyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
836
8
33

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,250 publications
(926 citation statements)
references
References 15 publications
43
836
8
33
Order By: Relevance
“…Finally, the addition of increasing amounts of elastase to pure mediator had no effect on assays of MPO activity, IL-8 or LTB 4 (respectively, 103.4%, 96.4% and 106.2% of control value at 10 -6 M elastase). Low concentrations of elastase (#10 -9 M) had no significant effect on the measurement of SLPI (96.2% of control value at 10 -9 M elastase).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Finally, the addition of increasing amounts of elastase to pure mediator had no effect on assays of MPO activity, IL-8 or LTB 4 (respectively, 103.4%, 96.4% and 106.2% of control value at 10 -6 M elastase). Low concentrations of elastase (#10 -9 M) had no significant effect on the measurement of SLPI (96.2% of control value at 10 -9 M elastase).…”
Section: Resultsmentioning
confidence: 90%
“…In recent years, there has been increasing interest in the role of lung inflammation in the development and progression of a variety of lung diseases as diverse as pulmonary fibrosis [1], cystic fibrosis [2], idiopathic bronchiectasis [3], chronic obstructive pulmonary disease (COPD) [4] and asthma [5]. These studies have been facilitated by the widespread availability of commercial assays to measure the inflammatory mediators of interest.…”
mentioning
confidence: 99%
“…Lower airway IL-8 levels have been shown to increase with experimental rhinovirus type 16 infection in normal and asthmatic patients in some studies [29], but not in others [28]. However, COPD patients already have upregulated airway IL-8 levels when stable, possibly due to their high sputum neutrophil load [30], and so a further increase in IL-8 concentration at COPD exacerbation would be unlikely. Using a transformed epithelial cell line, rhinovirus has been shown to attach to airway epithelium [31] and to increase IL-6 production from epithelial cells through a nuclear factor-kB-dependent transcription pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…It induces chronic inflammatory changes associated with an increase in a variety of defence mechanisms including antioxidants levels [141]. TNF-a is an important inflammatory mediator in COPD and ARDS and is present in increased amounts in the bronchoalveolar lavage fluid (BALF) and sputum of COPD patients [142]. Recently, various investigators [86,143] have shown rapid depletion of intracellular GSH by TNF-a exposure in epithelial and endothelial cells in vitro, due to oxidation of GSH to GSSG.…”
Section: Effect Of Pro-and Anti-inflammatory Mediatorsmentioning
confidence: 99%